The combination of bleomycin with suicide or interferon-B gene transfer is able to efficiently eliminate human melanoma tumor initiating cells - Fondello, Chiara (2016)
We explored the potential of a chemogene therapy combination to eradicate melanoma tumor initiating cells, key producers of recurrence and metastatic spread. Three new human melanoma cell lines, two obtained from lymph nodes and one from spleen metastasis were established and characterized. They were cultured as monolayers and spheroids and, in both spatial configurations they displayed sensitivity to single treatments with bleomycin (BLM) or human interferon-β (hIFNβ) gene or herpes simplex virus thymidine kinase/ganciclovir suicide gene (SG) lipofection. However, the combination of bleomycin with SG or hIFNβ gene transfer displayed greater antitumor efficacy. The three cell lines exhibited a proliferative behavior consistent with melan A and gp100 melanoma antigens expression, and BRAF V600E mutation. BLM and both genetic treatments increased the fraction of more differentiated and treatment-sensitive cells. Simultaneously, they significantly decreased the sub-population of tumor initiating cells. There was a significant correlation between the cytotoxicity of treatments with BLM and gene transfer and the fraction of cells exhibiting (i) high proliferation index, and (ii) high intracellular levels of reactive oxygen species. Conversely, the fraction of cells surviving to our treatments closely paralleled their (i) colony and (ii) melanosphere forming capacity. A very significant finding was that the combination of BLM with SG or hIFNβ gene almost abrogated the clonogenic capacity of the surviving cells. Altogether, the results presented here suggest that the combined chemo-gene treatments are able to eradicate tumor initiating cells, encouraging further studies aimed to apply this strategy in the clinic.